The movies as a world force : American silent cinema and the utopian imagination - Friedman, Ryan Jay (Rutgers University Press, 2019)
The Movies as a World Force is the first analysis of utopian cinema writing; situating it in its proper intellectual contexts, theology, and political philosophy; and illustrating the ways in which its utopian imagination shapes and is shaped by the era's most prestigious film genre, the historical crowd epic.
Keywords: Utopias in motion pictures.; Silent films -- United States -- History.; Utopies au cinéma.; Films muets -- États-Unis -- Histoire.; PERFORMING ARTS -- General.; Silent films; Utopias in motion pictures; United States; History